Defect reorganization induced by pulsed magnetic field in porous InP - Milenin, V.V.; Red’ko, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
We present results of investigations of the effect caused by weak magnetic field (B = 60 mT) in porous InP crystals of impurity-defect composition. This effect was found when studying the spectra of radiative recombination within the range 0.6 to 2.0 µm at 77 K. It was obtained that field influence initiates long-term changes in the intensity of radiative recombination inherent to centers of different nature. A possible mechanism of observed transformation is discussed.